Rutile phase dominant TiO2 formed by thermal treatment and its high photocatalytic activity under narrow spectrum ultraviolet light emitting diodes. (31st October 2018) - Natarajan, Kalithasan; Natarajan, Thillai Sivakumar; Bajaj, Hari C; Tayade, Rajesh J
Abstract: The photocatalysts having different phase composition (Anatase/Rutile) used in this study were obtained by calcination of Degussa P25 titanium dioxide catalyst at different temperatures namely 500, 600, 700, and 800 °C. The calcined catalysts were characterized using Powder x-ray diffraction (PXRD), UV–visible-diffuse reflectance spectroscopy (UV-vis-DRS), Brunauer–Emmett–Teller (BET) Surface area, Scanning electron microscope (SEM), Transmission electron microscope (TEM), and Fourier transform infrared spectroscopy (FTIR). The photocatalytic activity of the P25 catalysts were studied by degradation of malachite green (MG) dye solution under irradiation of narrow spectrum ultraviolet light emitting diodes (UVLED) of 390–410 nm range using locally designed photocatalytic reactor. Among the catalysts utilized, higher degradation percentage (99%) was achieved in the case of calcined catalyst (P25-700) which has the anatase (ca. 26%) and rutile (74%) phase percentage. Fluorescence analysis was also studied to confirm the higher hydroxyl radical generation under irradiation of narrow spectrum UVLED irradiation in presence of P25-700 catalyst during photocatalytic reaction which leads to higher photocatalytic degradation of MG as compared to other catalysts. The complete degradation of MG dye has also been confirmed using chemical oxygen demand (COD) and total organic carbon (TOC) analysis.